The role of apoliproteins in lipid metabolism and atherogenesis: aspects on man an mice - Kreuzer, Jörg; Hodenberg, Eberhard von (Journal of hypertension, 1994)
An abstract is unavailable. This article is available as a PDF only.
Gesehen am 30.10.2025